Performance Analysis and Energy Conservation of PV Based Hybrid Power System - Rajput, Saurabh Kumar; Dheer, Dharmendra Kumar (Distributed Generation & Alternative Energy Journal, 2022)
The increase in energy consumption due to population expansion and scarcity of fossil fuels is happening simultaneously in developing countries like India. In this regard, commercial buildings are increasingly required to employ renewable energy sources (like PV) and conserve the energy for improving energy efficiency. This research article examines the performance of such PV-based hybrid power system, consists of 11 kV grid supply, 100 kWp PV plant & 200 kVA diesel generator. The results indicate that the addition of 68.34 kVAr shunt capacitor bank to Automatic Power Factor Compensation (APFC) panel, keeps the Power Factor (PF) unity and also eliminates the PF penalties in electricity bills. The maximum demand (MD) saving Rs 54528.00 (INR) on annual basis is achieved after the integration of PV with low voltage (433 V) distribution system and grid supply (11 kV). This integration has also reduced the average transformer loading to 64.73% and improved the transformer life. However the development of high current harmonics (average value 47.10%) must be reduced to ensure the life of the electrical load.